Structural features and antitumor activity of a purified polysaccharide extracted from Sargassum horneri - Shao, P.; Liu, J.; Chen, X.; Fang, Zhongxiang; Sun, P. (Elsevier, 2015)
A polysaccharide fraction (SHPSA) was obtained from Sargassum horneri by hot-water extraction and sequential purification of anion-exchange chromatography and gel-filtration chromatography. SHPSA was found to be a neutral polysaccharide fraction with an average molecular weight of 5.78 × 105 Da and composed of T-d-Glcp, 1,3-d-Glcp, 1,6-d-Glcp and 1,3,6-d-Glcp in a molar percentage of 1.00:4.17:1.17:0.89, respectively. Based on the results from chemical analysis, NMR, and SHPSA was determined to be a glucan with β-(1 → 6) side chains linked to a β-(1 → 3) backbone with relatively few branch points. Moreover, SHPSA could inhibit the growth of human colon cancer DLD cells in a dose-dependent manner by inducing the apoptosis of DLD cells. So, SHPSA was promising for future use as a natural antitumor agent.